TGF-β3 suppresses melanogenesis in human melanocytes cocultured with UV-irradiated neighboring cells and human skin. Issue 2 (August 2020) - Moon, Hye-Rim; Jung, Joon Min; Kim, Su Yeon; Song, Youngsup; Chang, Sung Eun
Highlights: TGF-β3 decreases melanin content in UVB-treated melanocyte-keratinocyte-fibroblast coculture. TGF-β3 reduces melanin content in UVB-treated ex vivo human skin. TGF-β3 decreases melanogenesis via the ERK pathway. Abstract: Background: Ultraviolet radiation (UVR) is the most well-known cause of skin pigmentation accompanied with photoaging. Transforming growth factor (TGF)-β1 was previously shown to have anti-melanogenic property; however, it can induce scarring in skin. Objective: We investigated the effect of TGF-β3 on melanogenesis in human melanocytes cocultured with UV-irradiated skin constituent cells, and UV-irradiated human skin. Methods: UVB irradiation or treatment with stem cell factor (SCF) and endothelin-1 (ET-1) was applied to human melanocytes cocultured with keratinocytes and/or fibroblasts and ex vivo human skin. Mechanistic pathways were further explored after treatment with TGF-β3. Results: While UVB irradiation or SCF/ET-1 enhanced melanogenesis, TGF-β3 effectively inhibited melanin accumulation and tyrosinase activity via downregulation of the extracellular signal-regulated kinase (ERK)/microphthalmia-associated transcription factor (MITF) pathway. TGF-β3 increased the expression of differentiation markers of keratinocytes. Conclusion: TGF-β3 effectively suppressed UVR-stimulated melanogenesis indicating that topical TGF-β3 may be a suitable candidate for the treatment of UV-associated hyperpigmentation disorders.